Analysis of the training of Sports Instructors in Huelva - José Antonio Rebollo González; Pedro Sáenz-López Buñuel (Federación Extremeña de Balonmano; University of Extremadura, 2011)
Abstract   All studies show that in our days, most people who do physical activities do it for recreation. Therefore it is necessary to train training of experts with qualifications to fulfill the needs of the participants. In this study we examined the initial training of Sport Instructor, through interviews with experts, who provided suggestions for improvement in terms of content, organization, methodology, etc.